Multi-scale modelling of energetic particle dynamics and radio signatures in coronal and heliospheric plasmas - Husidic, Edin (fi=Turun yliopisto|en=University of Turku|, 2025)
Solar Energetic Particles (SEPs) accelerated during space weather events such as solar flares, Coronal Mass Ejections (CMEs), and corotating interaction regions, can reach energies up to several GeV per nucleon for ions and several tens MeV for electrons, thereby posing significant risks to satellites, astronauts, and ground-based systems. Understanding SEP acceleration and transport, along with their associated radio signatures, is crucial for enhancing space weather forecasts and mitigation strategies. This thesis presents, in three stages, a novel, physics-based framework to simulate the acceleration, transport, and radio emission of SEPs in realistic solar wind and coronal environments. Building on an earlier implementation in which the MagnetoHydroDynamic (MHD) model EUHFORIA has been coupled with the focused transport code PARADISE, we first replace EUHFORIA with the more advanced inner heliospheric solar wind MHD code Icarus, which supports localised grid refinements and higher shock resolutions via adaptive mesh refinement. Next, to study SEP and CME dynamics below 0.1 au, the framework is extended into the corona using the COCONUT MHD model. Finally, we integrate the Ultimate Fast Gyrosynchrotron Codes to compute radio emission from energetic electrons trapped in a CME flux rope. Applications for each stage demonstrate significant advances in modelling particle dynamics in both the corona and heliosphere. The framework enables realistic simulations of particle acceleration at finely resolved shocks, investigation of particle confinement and escape in low-coronal magnetic flux ropes, and direct linkage of these processes to observable type IV radio emission, offering valuable diagnostic capabilities for CME magnetic fields and SEP properties near the Sun. Moreover, the integration of coronal and heliospheric domains represents a key step towards global-scale simulations of CME and SEP events from the solar surface to Earth’s orbit and beyond, supporting future efforts to untangle the complex, interconnected processes governing space plasmas.